Syntheses and Biological Activity of Some 3, 5-Driaryl-4h-1, 2, 4-Triazole Derivatives - RAM JANAM SINGH; DHARMENDRA KUMAR SINGH (International Journal of Pharma and Bio Sciences, 2010)
The syntheses of a series of novel 3, 5-diaryl-4-4H-1, 2, 4-triazole derivatives are described. A total of eight new compounds were synthesized and characterized by spectral and elemental analyses. Some compounds were screened for antibacterial activity against S. aureus, E. coli, B. subtilis and P. aeruginosa. Compounds containing aryl substituents at position six and the 1, 2, 4- triazole moiety at position one or two showed reasonable antibacterial activity.